Arsenic methylation metabolism and liver injury of acute promyelocytic leukemia patients undergoing arsenic trioxide treatment1. Issue 5 (31st August 2011) - Wang, Huihui; Xi, Shuhua; Liu, Zhuogang; Yang, Ying; Zheng, Quanmei; Wang, Fei; Xu, Yuanyuan; Wang, Yi; Zheng, Yi; Sun, Guifan
Abstract Although arsenic is effective in the treatment of acute promyelocytic leukemia (APL), as a well‐known environmental toxicant, the side effects of arsenic treatment and arsenic methylation metabolism of the patients are rarely reported. In this manuscript, we investigated 23 APL patients treated with 10 mg arsenic trioxide daily, detected the arsenic metabolites in urine samples collected on the 0, 10th, and 20th day of arsenic treatment. At the same time, liver function and blood routine examination were also investigated in these APL patients. We found that, urinary monomethylated arsenic proportion (MMA%) increased, but dimethylated arsenic proportion (DMA%), the first methylation ratio (FMR) and the secondary methylation ratio (SMR) decreased with consecutive administration of arsenic trioxide. After adjustment for age impact, no statistical difference was observed in urinary arsenic concentrations and arsenic methylation capacity between male and female at the same treatment time point. During arsenic trioxide treatment of APL, transient elevation of serum aminotransferases was found in the blood samples, which indicated that liver injury occurred and probably reversible. Leukocytosis developed in 5 of the 23 patients with the administration of arsenic trioxide. No statistical difference was observed in the other blood routine examination parameters. These results demonstrated that the capacity of arsenic methylation decreased and transient liver injury occurred during arsenic trioxide treatment of APL, which indicated that the side effects of clinical arsenic treatment can not be ignored. © Wiley Periodicals, Inc. Environ Toxicol, 2013.